Case report: Off-label use of low-dose perampanel in a 25-month-old girl with a pathogenic SYNGAP1 variant - Gupta, Siddharth; Hwang, Yun; Ludwig, Natasha; Henry, Julia; Kadam, Shilpa D. (Frontiers in Neurology, 2023)
Introduction Preclinical studies in a mouse model have shown that SYNGAP1 haploinsufficiency results in an epilepsy phenotype with excessive GluA2-AMPA insertion specifically on the soma of fast-spiking parvalbumin-positive interneurons associated with significant dysfunction of cortical gamma homeostasis that was rescued by perampanel (PER), an AMPA receptor blocker. In this single case, we aimed to investigate the presence of dysregulated cortical gamma in a toddler with a pathogenic SYNGAP1 variant and report on the effect of low-dose PER on electroencephalogram (EEG) and clinical profile. Methods Clinical data from physician's clinic notes; genetic testing reports; developmental scores from occupational therapy, physical therapy, speech and language therapy evaluations; and applied behavioral analysis reports were reviewed. Developmental assessments and EEG analysis were done pre- and post-PER. Results Clinically, the patient showed improvements in the developmental profile and sleep quality post-PER. EEG spectral power analysis in our patient revealed a loss of gamma power modulation with behavioral-state transitions similar to what was observed in Syngap1+/− mice. Furthermore, the administration of low-dose PER rescued the dysfunctional cortical gamma homeostasis, similar to the preclinical study. However, as in the epileptic mice, PER did not curb epileptiform discharges or clinical seizures. Conclusion Similar to the Syngap1+/− mice, cortical gamma homeostasis was dysregulated in the patient. This dysfunction was rescued by PER. These encouraging results necessitate further validation of gamma dysregulation as a potential translational EEG biomarker in SYNAP1-DEE. Low-dose PER can be explored as a therapeutic option through clinical trials.